2019
DOI: 10.15252/embj.2018100020
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the heart specific SERCA 2a Ca 2+ATP ase

Abstract: The sarcoplasmic/endoplasmic reticulum Ca 2+ -ATPase 2a (SERCA2a) performs active reuptake of cytoplasmic Ca 2+ and is a major regulator of cardiac muscle contractility. Dysfunction or dysregulation of SERCA2a is associated with heart failure, while restoring its function is considered as a therapeutic strategy to restore cardiac performance. However, its structure has not yet been determined. Based on native, active protein purified from pig ventricular muscle, we present the first crystal structures of SERCA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Calcium-ion homeostasis is an important factor in maintaining heart health. SERCA2a, the main subtype of sarcoplasmic reticulum calcium ATPase in cardiomyocytes, plays a major role in the regulation of cardiac contractility [ 78 ]. SERCA2a transports cytoplasmic calcium ions into the sarcoplasmic reticulum (SR).…”
Section: Potential Mechanisms Involved In M6a Methylation-mediated Re...mentioning
confidence: 99%
“…Calcium-ion homeostasis is an important factor in maintaining heart health. SERCA2a, the main subtype of sarcoplasmic reticulum calcium ATPase in cardiomyocytes, plays a major role in the regulation of cardiac contractility [ 78 ]. SERCA2a transports cytoplasmic calcium ions into the sarcoplasmic reticulum (SR).…”
Section: Potential Mechanisms Involved In M6a Methylation-mediated Re...mentioning
confidence: 99%
“…The SERCA-PLB complex was modeled from crystal structures of SERCA1a, the skeletal muscle isoform for which many conformations are available (26). This isoform has high homology to the cardiac-specific calcium pump, SERCA2a, and the recently published first structure of SERCA2a showed that the known PLB-binding site is highly conserved between these isoforms (63). Here we generated models starting from three different SERCA1a structures: 1SU4 (43), representing an E1 calcium-bound state; 3AR4 (42), representing an E2 calcium-free state; and 4KYT (12), representing a calcium-free state bound to PLB.…”
Section: Preparation Of Starting Structuresmentioning
confidence: 99%
“…The activity of sarcoplasmic/endoplasmic reticulum Ca 2+ -ATPase 2 alpha (SERCA2a) tightly regulates cardiac contractility by performing active reuptake of cytoplasmic Ca 2+ . Whereas impaired SERCA2a function is associated with HF, restoring the function of SERCA2a represents a therapeutic strategy to recover cardiac performance (Bers, 2002;Sitsel et al, 2019). SERCA2a controls cardiac muscle relaxation by regulating the amount of Ca 2+ released during myocardial contraction, which, in turn, determines the extent of cardiac muscle contraction (Bers, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several transmembrane micropeptides regulate the activity of SERCA2a in the heart, including phospholamban (PLB) (MacLennan and Kranias, 2003), cAMP-dependent protein kinase (PKA), and dwarf open reading frame (DWORF) (Nelson et al, 2016). If SERCA2a expression and PLB phosphorylation are reduced, Ca 2+ uptake into the sarcoplasmic reticulum (SR) will be negatively affected, thereby impairing the contractile performance of the heart (Sitsel et al, 2019). Consequently, a reduction in SERCA2a activity can lead to the progressive deterioration of cardiac contractility in patients with HF.…”
Section: Introductionmentioning
confidence: 99%